Space Truss Masonry Walls With Robotic Mortar Extrusion. (April 2019) - Duballet, R.; Baverel, O.; Dirrenberger, J.
Abstract: This work presents a generalized method for robotic mortar extrusion, allowing the fabrication of structural-insulating walls of novel performances. It involves two distinct steps that are to be simultaneously automated: extrusion of a specifically formulated mortar, and assembly of adequately shaped insulating blocks. Here, the layer by layer approach of concrete printing is renewed by using insulating blocks as support for the extrusion. The volumetric space of the wall is divided by an adequate space tessellation, dividing it in polyhedra. They become insulating blocks, on the edges of which mortar is extruded. The set of edges then forms a space truss, of great mechanical efficiency. "Printable" mortar is crucial to the system for the blocks could not withstand the hydrostatic pressure of fresh mortar without additional form-work features, once a few meters height has been reached. This approach renews traditional confined masonry, allowing for geometric complexity and automation.